Potential activity of ethanolic extract of Boesenbergia rotunda (L.) rhizomes extract in accelerating wound healing in rats - Mahmood, A.A.; Mariod, A.A.; Abdelwahab, S.I.; Ismail, S.; Al-Bayaty, F. (Academic Journals, 2010)
This study was conducted to evaluate the effects of topical application of ethanol extract of Boesenbergia rotunda rhizomes on the rate of wound healing closure and histology of healed wound. An area of uniform wound 2.00 cm in diameter using circular stamp, was excised from the nape of the dorsal neck of all rats with the aid of round seal. The animal groups were topically treated with 0.2 ml of each vehicle (gum acacia), Intrasite gel, 100 and 200 mg/ml of ethanol extract, respectively. Macroscopically, wound dressed with rhizomes extract and Intrasite gel significantly healed earlier than those treated with vehicle. Histological analysis of healed wounds dressed with rhizomes extract showed comparatively less scar width at wound closure and healed wound contained less inflammatory cells and more collagen with angiogenesis compared to wounds dressed with vehicle. In conclusion, wounds dressed with rhizomes extract significantly enhanced the acceleration of wound healing enclosure in rats.